Phytochemical evaluation and cytotoxic activities of stem bark and leaf extracts of Mesua assamica - Hazlina Ahmad Hassali,; Chan, Gomathi; Wan Hamirul Wan Bahrin,; Zainah Adam,; Daryl Jesus Arapoc,; Rosniza Razali,; Azfar Hanif Abd Aziz,; Khalijah Awang, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Natural products and their derivatives have historically been invaluable as a source of therapeutic agents. The Mesua (Calophyllaceae) has been known to produce various new chemical compounds of medicinal values. Some Mesua species have yielded new potential anticancer agents that are important to the pharmaceutical industry. In this research, phytochemical constituents, antioxidant and cytotoxic activities of different solvent extracts of Mesua assamica stem bark and leaves were evaluated. The stem bark and leaves of M. assamica were successively extracted in hexane, ethyl acetate and methanol. Qualitative phytochemical analysis showed that most of the M. assamica extracts consist of important phytochemicals, namely, anthraquinones, terpenoids, flavonoids, saponins, tannins, phlobatannins, alkaloids, cardiac glycosides, glycosides, decreasing sugars, steroids, lipids, phenols, coumarins, carbohydrates, proteins, and betacyanin indicating its potential for medicinal use. Quantitative determination of total phenolics, total flavonoids, and in vitro antioxidant activities through DPPH assay of M. assamica extracts have been achieved by utilizing colorimetric methods. In vitro cytotoxic evaluation through MTT assay induction against human breast MCF-7 cancer cell lines exhibited that hexane extracts were found to have IC50 value below 30 μg/mL and conferred effectiveness in inducing cell death MCF-7. The diversity of phytochemicals present suggests that the stem bark and leaves of M. assamica could serve as a supply of potentially valuable medications. Exploiting the plant’s pharmacological qualities will necessitate more study on the isolation, purification, and identification of bioactive components.